Centroidal-polygon: a new modified Euler to improve speed of resistor-inductor circuit equation - Nur Shahirah Zulkifli; Nooraida Samsudin; Suzanna Ridzuan Aw; Wan Farah Hanan Wan Osman; Shahreen Kasim; Tole Sutikno (Institute of Advanced Engineering and Science, 2021)
Two types of first-order circuits are resistor-capacitor (RC) and resistorinductor (RL). This paper focuses on the RL circuit equation. The centroidalpolygon (CP) scheme will be tested using SCILAB 6.0 software. This new scheme (CP scheme) is addressed to improve the speed. For the first order circuit equation, the complexity is focused on the time complexity, which is speed of the time taken to complete the simulation in the electrical part. The CP scheme is compared with the previous studies, polygon (P) and harmonic-polygon (HP). The result shows that the CP scheme is less computational and an alternative to solve the first order circuit equation, and get the result quickly compared with the previous research.